133 Investigating the Utilization Rate of Fertility Preservation Services Amongst Transgender and Gender Diverse Patients. (April 2022) - DSouza, Karen; Soo Lee, Yeon; Vasilev, Dzhuliyan J.; Allyse, Megan; Ainsworth, Alessandra; Davidge-Pitts, Caroline J.; Enders, Felicity; Khan, Zaraq
Abstract : OBJECTIVES/GOALS: Fertility preservation (FP) allows transgender and gender diverse (TGD) patients undergoing gender-affirming therapy to pursue genetic parenthood. Barriers to care exist leading to its underutilization; while these barriers to care have been investigated, the true utilization rates of FP services by TGD patients are unknown. METHODS/STUDY POPULATION: This study includes a retrospective chart review of adult and pediatric patients from Mayo Clinics Transgender and Intersex Specialty Care Clinic who have provided research authorization. We will assess if FP was discussed and review if the patients proceeded to make appointments with either the Department of Reproductive Endocrinology & Infertility or the Department of Urology. FP terms include semen cryopreservation, sperm extraction, sperm aspiration, testicular tissue cryopreservation, oocyte cryopreservation, embryo cryopreservation, and ovarian tissue cryopreservation. Patient demographic data will be collected to determine associations between utilization rate and age, sex recorded at birth, gender identity, race, ethnicity, and variables related to socioeconomic determinants of health. RESULTS/ANTICIPATED RESULTS: We hypothesize that the rate of FP utilization will be higher for patients who begin to affirm their gender at the age of 25 or older, and for those seeking feminization treatment in comparison to pre-pubescent adolescents, young adults, and transgender men. Of FP options, semen cryopreservation will be most utilized, followed by oocyte cryopreservation; both will be more utilized than embryo cryopreservation, sperm extraction, sperm aspiration, testicular tissue cryopreservation, and ovarian tissue cryopreservation. Employment, and insurance status and coverage, will play a role in FP service utilization after initial consult. This study was approved by Mayo Clinics Institutional Review Board. Data on N=611 patients is expected to be abstracted and analyzed prior to Translation 2022. DISCUSSION/SIGNIFICANCE: This study will be one of the first to examine the rate of FP utilization by TGD patients with respect to the age and timing of gender-affirming therapy initiation. Understanding the rate of utilization of FP services will allow for the creation of age-appropriate education materials for TGD patients pursuing gender affirmation and FP at Mayo Clinic.